2000
DOI: 10.1055/s-2000-7874
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Treatment and Outcome of Patients with Askin-Tumors

Abstract: Askin tumors are highly malignant small-round-cell tumors of the thoracopulmonary region, which occur rarely. Therefore, we report on our experiences with eight patients (5 male, 3 females), who were treated in our department between 11'94 and 10'97 (age: 9-40 years, mean age: 20.5 years). All Askin tumors were diagnosed by histological and immunohistochemical examinations as well as molecular genetic proof of characteristic translocations. In all patients, the tumor arose from the chest wall, infiltrating adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 8 publications
2
35
1
Order By: Relevance
“…In addition, the characteristics of the disease phenotype were identified using immunohistochemical analysis, which demonstrated positive expression of CD99, NSE, S-100 and vimentin protein, while tests for CK, CgA, Syn, LCA, TTF-1 provided negative results. These results are in accordance with previous reports (3,16,17).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In addition, the characteristics of the disease phenotype were identified using immunohistochemical analysis, which demonstrated positive expression of CD99, NSE, S-100 and vimentin protein, while tests for CK, CgA, Syn, LCA, TTF-1 provided negative results. These results are in accordance with previous reports (3,16,17).…”
Section: Discussionsupporting
confidence: 83%
“…For immunohistochemical analysis, the tumor was previously reported to be positive for several neural markers including NSE, CD99 and vimentin (13,15). Cellular and molecular genetics studies have suggested that PNET has a characteristic chromosomal translocation t (11:22) (q24; q12), which provides an additional firm diagnostic criterion for Askin's tumor (16,17). In addition, the characteristics of the disease phenotype were identified using immunohistochemical analysis, which demonstrated positive expression of CD99, NSE, S-100 and vimentin protein, while tests for CK, CgA, Syn, LCA, TTF-1 provided negative results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(7) Distant metastasis has been known to spread to lungs, mediastina and retroperitoneal nodes, bones, diaphragm, liver, adrenals, sympathetic nerve chain and brain. (8) (9) DISCUSSION OF MANAGEMENT Peripheral Primitive Neuroectodermal Tumours (PNETs) are a group of small round cell malignancies with neural crest origin that arise outside central and sympathetic nervous system. (10) It is a rare disease in children as well as in adults.…”
Section: Pathological Discussionmentioning
confidence: 99%
“…Operation, combination chemotherapy or radiotherapy has been selected, but not satisfactory (15,18). This tumor is thought to require an aggressive multimodality treatment consisting of preoperative and postoperative chemotherapy, radical surgical resection and postoperative irradiation, which may be performed preoperatively in selected cases (18). …”
Section: Discussionmentioning
confidence: 99%